Effects of Cecropin Transgenesis and Interspecific Hybridization on the Resistance to Ichthyophthirius multifiliis in Channel Catfish and Female Channel Catfish × Male Blue Catfish Hybrids. (28th June 2019) - Elaswad, Ahmed; Khalil, Karim; Ye, Zhi; Alsaqufi, Ahmed; Abdelrahman, Hisham; Su, Baofeng; Perera, Dayan A.; Dong, Sheng; Abass, Nermeen; Dunham, Rex
Abstract: The resistance of Channel Catfish Ictalurus punctatus, hybrid catfish (female Channel Catfish × male Blue Catfish I. furcatus [CB hybrids]), and Channel Catfish and hybrid catfish expressing the introduced cecropin B gene to Ichthyophthirius multifiliis infestation was investigated in two experiments. In experiment I, four fingerling groups were challenged, including cecropin‐transgenic Channel Catfish, cecropin‐transgenic CB hybrids, non‐transgenic Channel Catfish, and non‐transgenic CB hybrids. Non‐transgenic Channel Catfish survived for a shorter time than the other three groups. Survival rate was significantly different between non‐transgenic Channel Catfish and the other groups, which had similar survival rates. In experiment II, non‐transgenic CB hybrids had a less severe infestation than non‐transgenic Channel Catfish. Mortality rates were 62.4% and 40.2% for non‐transgenic Channel Catfish and CB hybrids, respectively. The mean survival time for non‐transgenic hybrids was significantly longer (>5 d) than that of non‐transgenic Channel Catfish. The results suggest that genetic enhancement of Ichthyophthirius resistance can be accomplished in Channel Catfish by either cecropin transgenesis or interspecific hybridization. In addition to survival rate, improving survival time is important because the extension of survival time provides greater opportunity to apply treatments to stop the protozoan infestation.